The Efforts of PAI Teachers in Analyzing Student Knowledge Through Diagnostic Assessment at SMP Aisyiyah Terpadu Pagar Alam - Tulhuiriah, Ulfa; Kalsum, Nyayu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the efforts of PAI teachers in analyzing student knowledge through Diagnostic Assessment at SMP Aisyiyah Terpadu Pagar Alam. This research uses a qualitative method with a descriptive approach. The population of this study includes all teachers at SMP Aisyiyah, and the sample consists of PAI teachers teaching the Merdeka curriculum at SMP Aisyiyah Terpadu Pagar Alam, selected using Purposive Sampling technique along with descriptive qualitative methods. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out using data reduction, data display, and verification or conclusion drawing. The results of this study show that Diagnostic Assessment has been implemented at SMP Aisyiyah Terpadu Pagar Alam, but in practice, there is still a lack of synchronization between the planning in the teaching module and its implementation. Supporting factors for the implementation of diagnostic assessments include support and supervision from the curriculum vice-principal. With the implementation of diagnostic assessments, teachers can adjust lessons to meet student needs and align learning with the objectives to be achieved. The challenges faced in the implementation of diagnostic assessments include a lack of teacher training, which results in teachers not conducting more engaging diagnostic assessments, and difficulties arise when encountering students who do not understand or grasp the material to be taught in lessons.